GPR method as a non-invasive method for investigating organic soils deposited under designed road construction - Konopko, Mariola; Wysocka, Małgorzata Ewa (International Conference “Environmental Engineering”, 2017)
GPR method is a non-invasive technique for ground exploration which detects subsurface objects and assesses their presence, as well as provides information about the geological structure of investigation site. Ground penetrating radar method belongs to the group of geophysical methods as it uses electromagnetic waves. GPR technique takes advantage of the differences between the dielectric constants, specific for the material under analysis. One of the factors that are essential to record reliable data is a clear contrast between the dielectric constant of investigated object and its surroundings. One of the major advantages of GPR is that it does not damage ground surface as well as it is completely non-invasive and safe for the environment. Moreover, the method is particularly useful in the design and realisation process of linear objects, for among the multiple aspects of its utilization there is recognition of low earing organic soils. The discontinuous nature of traditional methods makes it difficult to precisely specify ground layering as well as accurately locate potential anomalies. The analysis carried out in this study shows that GPR technique can detect the boundaries of soil layers, which considerably simplifies ground assessment.
Keywords: ground penetrating radar method (GPR); non-invasive ground investigation; organic soils